Hungarians and the Turkic people before Ottomans - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2022)
The Finno-Ugric Hungarians made contact with people from the Turkish language group not later as in present-day Bashkiria. It was their original homeland, which was mentioned as the Great or Eastern Hungary by the medieval chroniclers. The Turkic people lived on the Great Steppe in that time, therefore the name of the Turks was a synonym of the nomads. However, in the Byzantine sources it were the Hungarians who were called The Turks. They settled in the region of the Azov Sea together with a branch of the Bulgarian Onogurs, noted in the Arabian sources as s.k.l, and later known as the Szeklers. They got under the political dependency of the Khazars. The Slavic name of the Hungarians *Ągri, from which the Latin name of the Hungari and the Polish Węgrzy was derived, descended from the name of the Onogurs. It seems that the Hungarian tribal commonwealth, which originally wandered to the Maeotidian Steppes and afterwards migrated to the Carpathian Basin, was multiethnical, with great participation of the Turkic population (such as the Szeklers and the Kabars). This people was Magyarized, but left elements of the own historical consciousness to the Hungarians, such as the memory of Attila, which was the basis of the eruditional story of the Hunnic-Hungarian identity by Simon of Kéza. Nevertheless, the Hungarian state preserved its multiethnical character, which generated problems only in the 19th century, a period of growth of the modern nationalisms, which resulted in the disintegration of the state in 1918.